The effect of operating conditions on turbidity removal by polymeric flocculant - Miyajima, Takumi; Kadooka, Hiroto; Tanaka, Takanori; Jami, Mohammed Saedi; Iwata, Masashi (2016)
Since there are many factors which influence the process of flocculation by polymeric flocculant, the scientific understanding of the flocculation mechanism is still under discussion. We have proposed a simple bridging model which expresses flocculation under various additive manners of the flocculant and enables visual understanding of qualitative trends of the flocculation system. In this study, from the simulated results based on the model and experimental data, we obtained the following knowledge. 1) The intermittent addition of polymeric flocculant gives better and reproducible turbidity removal. 2) The optimum dosage, which shows the minimum turbidity at a given manner of addition, increases as the number of doses under the intermittent addition increases. 3) In much lower (or higher) dosage than the optimum dosage, the reproducibility of turbidity removal is satisfactory. All these findings are originated from the difference of probability of bridging formation among particles under various additive manners.